2016
DOI: 10.7150/ijms.13264
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Spectrum of TBX5 Mutation in Patients with Lone Atrial Fibrillation

Abstract: Atrial fibrillation (AF), the most common type of cardiac rhythm disturbance encountered in clinical practice, is associated with substantially increased morbidity and mortality. Aggregating evidence demonstrates that abnormal cardiovascular development is involved in the pathogenesis of AF. A recent study has revealed that the TBX5 gene, which encodes a T-box transcription factor key to cardiovascular development, was associated with AF and atypical Holt-Oram syndrome. However, the prevalence and spectrum of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 77 publications
0
9
0
Order By: Relevance
“…The study participants experienced a comprehensive clinical investigation, including individual and familial history, detailed physical examination, standard 12-lead electrocardiogram and cardiac echocardiography as well as review of medical records. Diagnosis and classification of AF was made as previously described 14 . Subjects with hypertension, coronary heart disease, valvular heart disease, congenital heart disease, congestive heart failure, metabolic disorders, or any other recognized risk factor of AF were excluded from the study.…”
Section: Methodsmentioning
confidence: 99%
“…The study participants experienced a comprehensive clinical investigation, including individual and familial history, detailed physical examination, standard 12-lead electrocardiogram and cardiac echocardiography as well as review of medical records. Diagnosis and classification of AF was made as previously described 14 . Subjects with hypertension, coronary heart disease, valvular heart disease, congenital heart disease, congestive heart failure, metabolic disorders, or any other recognized risk factor of AF were excluded from the study.…”
Section: Methodsmentioning
confidence: 99%
“…The reason for this diverse phenotype following the same mutation is still unclear. The cross-species alignment of TBX5 protein showed that the altered tryptophan residue is evolutionarily conserved throughout the vertebrates, indicating its functional importance [22]. The understanding of the genetic mutations is an important aspect in deciphering the consequential clinical phenotypes [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Ma et al, (2016) identified multiple loss-of-function mutations in TBX5 in multiple patients affected with AF. Wang et al, (2016) found a novel loss-of-function mutation in TBX5 in a case with AF. Guo et al, (2016) uncovered a new TBX5 loss-of-function mutation in an index patient with idiopathic AF.…”
Section: Introductionmentioning
confidence: 95%